Diversidade da avifauna e sua relação com a complexidade da paisagem urbana de Morrinhos, Goiás - (:unkn) unknown (Universidade Estadual de Goiás, 2017)
Urban development is rapidly expanding around the world, driving environmental change. The Cerrado, one of the richest savannahs in the world, has been suffering from the fragmentation, degradation and destruction of its habitat due to the expansion of agriculture and urbanization, and yet there is still insufficient knowledge about these effects in the bird community. Several studies have been carried out in urban areas in recent years, most of which are in green areas, without considering the whole landscape. In order to identify the richness, abundance and composition of the avifauna throughout the study period, as well as to show how the complexity of the urban landscape can interfere in the distribution of these species, a survey was carried out between september/2015 and december/2016, in 64 points of the urban area of Morrinhos, south of Goiás, using the method of counting by points, being identified 166 species of birds, with an estimated wealth of 182.97 ± 5.03 species. The cumulative curve of species reached the asymptote, demonstrating that the area was sufficiently sampled. This study contributed 45 new records to the site, surpassing the estimated values, totaling 192 species for the city. The avifauna found has representatives typical of urban environments of the Cerrado, being predominantly composed of independent species of forest environments, with an omnivorous or insectivorous diet, and of low sensitivity to environmental disturbances, demonstrating that they are well conditioned to altered environments. The presence of species of conservation interest such as endemic and endangered species, as well as of rare or occasional species, justifies environmental management actions at urban level. Most of the richness and abundance of avifauna in food guilds and the distribution of species with some degree of dependence on forest environments have responded negatively with the intensity of urbanization, indicating a homogenization of avifauna toward the center of the city, where communities are more similar. However, avifauna presented a positive relation with the proximity of riparian vegetation in periurban regions, where they are more similar to natural environments and there is less fluctuation of availability of resources for birds in relation to drier environments. Nectarivorous species and frugivorous abundance were the only ones that showed a positive relation with urbanization, supposed to be benefited by exotic vegetable species and food of birds that are common in backyards, gardens and squares. The richness of carnivorous and omnivorous species were associated with nearby sites of intense traffic near the periphery, being open sites that favor foraging. The structural environmental variables explained better the variation of the species composition compared to the landscape variables, indicating that the birds respond individually to the environmental heterogeneity of these sites. Thus, urban green areas with more complex plant structure that retain part of the original vegetation are important to maintain a high diversity of species in the cities.
Diversity of avifauna and its relation with complexity of the urban landscape of Morrinhos, Goiás
Keywords: Aves; Cerrado; Urbanização; Estrutura ambiental; Homogeneização biótica; Análise de redundância; Birds; Cerrado; Urbanization; Environmental structure; Homogenization; Redundancy analysis; CIENCIAS BIOLOGICAS; CIENCIAS BIOLOGICAS::ECOLOGIA